1997
DOI: 10.1007/s002469900228
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Radiofrequency Ablation for Congenital Junctional Ectopic Tachycardia in Infancy

Abstract: Congenital junctional ectopic tachycardia (JET) is a difficult to treat arrhythmia with a variably poor response to pharmacologic intervention. We report on the successful treatment of a 17-day-old infant with JET via transcatheter radiofrequency ablation of the arrhythmogenic focus resulting in resolution of the tachycardia and maintenance of normal atrioventricular nodal function. Transcatheter radiofrequency ablation techniques should be considered in infants with life-threatening arrhythmia recalcitrant to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…The successful ablation sites were the para-Hisian area and midseptal region of the tricuspid annulus, as reported in previous studies 3, 4, 6. There are several ways to resolve JET, such as applying energy at the HBE recording site where the tachycardia rate can be decreased by the mechanical manipulation of the ablation catheter 15 or by the application of energy at the earliest retrograde atrial activation site when ventriculoatrial conduction is present 16 .…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…The successful ablation sites were the para-Hisian area and midseptal region of the tricuspid annulus, as reported in previous studies 3, 4, 6. There are several ways to resolve JET, such as applying energy at the HBE recording site where the tachycardia rate can be decreased by the mechanical manipulation of the ablation catheter 15 or by the application of energy at the earliest retrograde atrial activation site when ventriculoatrial conduction is present 16 .…”
Section: Discussionsupporting
confidence: 55%
“…There have been only 5 cases previously reported that have required CA during a patient's infancy 2, 3, 4, 6, 7. All 5 cases were successfully ablated, but the incidence of complications was high.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite these risks, radiofrequency ablation has been successfully performed in children [12], infants [13]and even neonates [14]. …”
Section: Introductionmentioning
confidence: 99%